Anaerobic conversion of phosphate by the mixed inoculum - GUO Xia-li; ZHENG Ping (浙江大学学报. 农业与生命科学版)
The conversion of phosphate into phosphine was an important biological reaction with potential value in application. The swine manure was mixed with two kinds of anaerobic activated sludge at the mass ratio of 3∶1∶1 and the mixture was used as inoculum in the batch experiment. The feasibility of cellulose, glucose and acetate as the electron donors for phosphate reduction was tested and the results showed that glucose was the most suitable one among them. With glucose as electron donor, the efficiency of phosphate reduction was twice as high as that of hypophosphite reduction at the same amount of electron donor. Theoretically the appropriate mass ratio of hydrated glucose to phosphate was 1∶2, but the measurement showed that 1∶1 was better. It was found that the phosphorus removal efficiency in the culture had well been correlated with the phosphorus content in the absorption solution. The population of sulphate-reducing bacteria but not fermentative bacteria should have some correlation with the phosphorus removal efficiency.